An investigation on the interface bond strength of geosynthetic-reinforced asphalt concrete using Leutner shear test. (20th October 2018) - Sudarsanan, Nithin; Karpurapu, Rajagopal; Amrithalingam, Veeraragavan
Highlights: Bond strength between asphalt and different types of geosynthetics was investigated. An equation is proposed to predict the interlayer bond strength of geosynthetic reinforced AC layers. Interlayer factor is introduced to understand the reduction or improvement in the bond strength. Abstract: The application of geosynthetics between the cracked asphalt pavement layer and new asphalt layers to retard reflective cracking has gained interest in the past decades. The performance of the interlayer system depends on its capacity to bond between the old and newly laid overlay layers. This study is taken up to evaluate the interlayer bond strength between the asphalt pavement layers that is reinforced with a geosynthetic product impregnated with asphalt as a tack coat material. Three geosynthetic reinforcement materials made of coir, jute, and glasgrid are used for the bond strength evaluation. The strength of the unreinforced (UR) interface samples are also evaluated for comparison. A trial pavement section was constructed to obtain the reinforced and unreinforced samples for the current research work. The main objective is to study the effects of these geosynthetic products at different temperatures on the interface shear strength behaviour of the reinforced asphaltic concrete layer. Leutner shear tests are employed for the estimation of the shear strength of these samples. The tests are performed at five different temperatures, −10, 0, 10, 20 and 30 °C to understand the thermal effects on the composite interface in the pavement. The shear tests conducted at a strain rate of 50 mm/min shows an increase in strength by 10–15% with change in temperature from −10 to 10 °C followed by 80% reduction in strength up to 30 °C. It is observed that the shear strength of the geosynthetic-reinforced interface samples reduces by 20–50% compared to the unreinforced samples depending upon the type of geosynthetic material. This paper proposes an equation to predict the Leutner shear strength at any temperature varying from −10 to 30 at the studied range of strain rates knowing the peak shear modulus of unreinforced samples at −10 °C and the reduction factor for the geosynthetic interlayer.